Problem of Synonym Translation: A Logical-Typological Approach - T. B. Barannikova; S. Kh. Bitokova; S. N. Khanbalaeva (Научный диалог)
The topicality of this article, carried out in line with the research of the “eternal” object of linguistics — synonymy, is determined by its weak investigation in the translation aspect. The subject of this study is the criteria for the equivalence of the translation of various types of synonyms in the belle-lettres context. The purpose of the article is to attempt a comprehensive, reasoned and generalizing coverage of the dependence of the ways of transmitting synonymous meanings in accordance with their belonging to a certain type, as well as taking into account the conditions for their presentation in the text. The scientific novelty of the study is due to its target setting and the development of a methodology for its implementation, based on a logical approach to the definition and classification of synonyms and a step-by-step translation analysis of the transfer of the differential features of various types of synonyms of the source language to the translator. The paper proves that the logical allocation of general and particular differential features of synonyms contributes to a clearer designation of the specifics of the translation of various types of synonyms in literary texts, as well as to the determination of its quality. The results obtained may be of interest to researchers in the field of synonymy theory and translation.